Penerapan Preventive Maintenance untuk Mengurangi Failure Product di Pangan Sejahtera Pabrik Tauco Kota Sukabumi - Zahra Syahmia Haidar; Erry Sunarya; Kokom Komariah (IPM2KPE, 2019)
The purpose of this study is to implement preventive maintenance activities to run in the company, to reduce the number of product failures that often occur in the prosperous food company in the Tauco city of Sukabumi. This study uses a qualitative descriptive method using the fishbone method or often referred to as a causal diagram by conducting unstructured interviews with employees who work in companies, especially in the production department. The results of the analysis conducted by the author using the Fishbone method to describe any abnormalities that occur in the company, especially in the engine for production by entering the dimensions of Preventive maintenance into the fishbone column and found several errors that were made in these dimensions in the field. Conclusion, The Implementation of Preventive Maintenance in Prosperous Food MSME of the Tauco Factory in Sukabumi City really works in accordance with the objectives that the author wants to reduce the Failure Product numbers which are quite high Keywords: Preventive Maintenance, Failure Product